2013
DOI: 10.1111/jne.12053
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Early Short‐Term Exercise in the Offspring of Obese Mothers are Accompanied by Alterations in the Hypothalamic Gene Expression of Appetite Regulators and FTO (Fat Mass and Obesity Associated) Gene

Abstract: Maternal overnutrition is implicated in the development of adult metabolic disease, and has been shown to alter the expression of genes involved in energy homeostasis. In the present study, we aimed to test whether a short period of voluntary exercise, followed by a sedentary period, would regulate hypothalamic markers involved in appetite. Adult female Sprague-Dawley rats were fed either normal chow or high-fat diet (HFD) ad lib. for 5 weeks, mated and continued on their assigned diet during gestation/lactati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Thus it would appear that cardiac FTO expression is affected by obesity and maternal programming, making it another interesting candidate gene for the CVD risk observed with maternal M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT obesity. FTO expression was also regulated by exercise; our lab has previously shown an effect of exercise on FTO expression in the hypothalamus [30], and here maternal exercise increased FTO expression in offspring of dams consuming chow.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 87%
“…Thus it would appear that cardiac FTO expression is affected by obesity and maternal programming, making it another interesting candidate gene for the CVD risk observed with maternal M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT obesity. FTO expression was also regulated by exercise; our lab has previously shown an effect of exercise on FTO expression in the hypothalamus [30], and here maternal exercise increased FTO expression in offspring of dams consuming chow.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 87%
“…Although no differences in central nervous system FTO gene expression between FTO genotypes in the cerebellum were found, there was indeed inter-individual variance in the FTO expression in this examined brain region [1]. Previous studies in mice have shown that the CNS expression of Fto can be weakened by exercise protocols [9]. This may also explain why population-based studies have shown that regular exercise attenuates the strength of the association between genetic variants in FTO and human obesity [10].…”
mentioning
confidence: 83%
“…FTO enhanced TCA cycle activity by regulating 2-oxoglutarate levels to promote differences in body energy metabolism 100. However, at present, there is another hypothesis that FTO may be a sensor of circulating amino acids rather than a sensor of 2-oxoglutarate 101-106. This action mainly occurs in FTO-deficient mice that exhibit developmental deformities.…”
Section: Fto and Energy Metabolismmentioning
confidence: 99%